Effect of age and fall status on lower-extremity muscle activation and joint torque and power in physically active women - Crozara, Luciano F. [UNESP]; Morcelli, Mary H. [UNESP]; Hallal, Camilla Z.; Marques, Nise R. [UNESP]; Spinoso, Deborah H. [UNESP]; Goethel, Márcio F. [UNESP]; Vieira, Edgar R.; Gonçalves, Mauro [UNESP] (SAGE Publications, 2016)
BACKGROUND: Lower-extremity strength and neuromuscular parameters that are more affected with age and in individuals more prone to fall still needs to be identified in healthy physically active adults. OBJECTIVE: To investigate the ability of joint torque and muscle activity parameters to differentiate between physically active women, young, older non-fallers and older fallers; and their correlation with the number of falls in older women. METHODS:Measures were taken from concentric contractions during isokinetic sagittal plane movements at 90°/s and 120°/s. EMG from the rectus femoris, vastus lateralis, biceps femoris, lateral gastrocnemius and tibialis anterior were recorded. RESULTS: Overall young women were stronger, more powerful and presented lower muscle activation than older women fallers and non-fallers (all p < 0.04). Older women fallers had lower knee flexion and extension peak torque (p < 0.033) and power (p < 0.045), lower ankle dorsiflexion power (p = 0.04) and higher rectus femoris activation (p = 0.033) at 90°/s than older women non-fallers; and all these variables were correlated with the number of falls (r = 0.32-0.49; p < 0.05). CONCLUSIONS: These findings may be useful for a better understanding of biomechanical risk factors for falls and for exercise-based fall prevention programs development.
Keywords: Accidental falls; Electromyography; Older adults; Strength